Effects of atmosphere on the oxidation state of iron and viscosity behavior of coal ash slag. (1st May 2019) - He, Chong; Bai, Jin; Kong, Lingxue; Xu, Jiang; Guhl, Stefan; Li, Xiaoming; Ge, Zefeng; Cao, Xi; Bai, Zongqing; Li, Wen
Highlights: The effect of atmosphere on the viscosity of fully molten slag is weak. The effect of metallic iron on slag viscosity is revealed for the first time. The metallic iron acts as crystal seed and promotes the anorthite crystallization. The crystallization of gehlenite is not influenced by metallic iron precipitation. Abstract: Viscosity behavior of coal ash slag in the slagging gasifier is the key for the stable operation. The oxidation state of iron in the slag is sensitive to the gas chemistry, which influences the viscosity behavior. The atmosphere in the gasifier varies from weak oxidizing to strong reducing, and the effect on slag viscosity behavior is still not available. In this study, viscosities of two coal ash slags of which chemical compositions located in the anorthite and gehlenite regions in the phase diagram SiO2 -Al2 O3 -CaO, were investigated under argon, mild reducing atmosphere and strong reducing atmosphere by the high temperature rotating viscometer. The wet chemical analysis was used to analyze the oxidation state of iron in coal ash slag. Thermodynamic calculation, XRD analysis and SEM-EDX were used to investigate crystallization behavior of the slags during cooling. The results show that the effect of atmosphere on the viscosity of fully molten slag is not obvious. The slag has the lowest viscosity value under the mild reducing atmosphere for the abundance of Fe 2+ (80% total iron). Under strong reducing atmosphere, the precipitation of metallic iron in coal ash slag increases slag viscosity as the content of network modifier declines. However, the effect of atmosphere on the slag viscosity is significant after the slag crystallizes. For the slag located in the anorthite region, the presence of metallic iron acts as crystal seed and significantly accelerates the crystallization of anorthite, resulting in a sharp increase of slag viscosity. However, the effect of atmosphere on the viscosity of slag located in the gehlenite region is not obvious because the crystallization propensity of gehlenite is too strong to be influenced by metallic iron precipitation.